White lotus. The complete first season [videorecording (DVD)] - White, Mike, 1970- (Home Box Office, 2022)
As the newest set of high class vacationers check into the exclusive White Lotus resort in Hawaii, manager Armand finds himself facing more than the usual excessive demands of one-percenters. He takes on momma's boys and workaholics with a professional facade, his coping mechanisms become as extreme as the pressure he's under, while the guests themselves unravel inside their toxic dynamics until the situations collide with incredible consequences.